VD_FINDINFO Pron / 2011 / 121 vom 8. November 2011 - VD Tribunal cantonal (2011)
SOCIÉTÉ À RESPONSABILITÉ LIMITÉE, ORGANISATIONEN GÉNÉRAL, REGISTRE DU COMMERCE | 731b CO, 941a CO, 154 al. 3 ORC, 154 ORC